Prognostic Value of Platelet to Lymphocyte Ratio in Sepsis: A Systematic Review and Meta-analysis. (6th June 2022) - Wang, Gancheng; Mivefroshan, Azam; Yaghoobpoor, Shirin; Khanzadeh, Shokoufeh; Siri, Goli; Rahmani, Farzad; Aleseidi, Samira
Abstract : The goal of this study was to conduct a systematic review of the literature on the relationship between peripheral blood platelet to lymphocyte ratio (PLR) and mortality in sepsis and to integrate the findings in a meta-analysis. An electronic search of three main databases was performed: PubMed, Embase, and Scopus on 19 December 2021. Finally, 16 studies comprising 2403 septic patients, including 1249 survivors and 1154 nonsurvivors, were included in this meta-analysis. We found that PLR levels were significantly higher in nonsurvivors than in survivors (random effect model: SMD = 0.72, 95% CI; 0.35–1.10, p < 0.001 ). However, significant heterogeneity was observed across the studies (I 2 = 94.1 %, p < 0.01 ). So, we used random effect model in our meta-analysis. In the subgroup analysis, according to mortality time, patients deceased during one month after sepsis had elevated levels of PLR compared to survivors (SMD = 1.03, 95% CI = 0.15 -1.92, p = 0.22 ). However, in-hospital mortality was not associated with PLR level (SMD = 0.41, 95% CI = − 0.18 -0.99, p = 0.175 ). Our findings support PLR to be a promising biomarker that can be readily integrated into clinical settings to aid in the prediction and prevention of sepsis mortality.